PELAKSANAAN REHABILITASI DAN TUNTUTAN GANTI RUGI DALAM TINDAK PIDANA KORUPSI - , M. KASIM; , Hery Firmansyah, S.H.,M.Hum.,MPA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The problem of corruption was not only on efforts to eradicate or its combating, but also related to other measures such as rehabilitation and compensation claims if the suspect or the accused not guilty of committing corruption. Therefore, the purpose of this research is to identify and analyze (1) rehabilitation and compensation claims in the fulfillment of corruption